Definition of anatomical zero positions for assessing shoulder pose with 3D motion capture during bilateral abduction of the arms - Rettig, Oliver; Krautwurst, Britta; Maier, Michael Wolfgang; Wolf, Sebastian Immanuel (BMC musculoskeletal disorders, 2015)
Surgical interventions at the shoulder may alter function of the shoulder complex. Clinically, the outcome can be assessed by universal goniometry. Marker-based motion capture may not resemble these results due to differing angle definitions.
Gesehen am 18.06.2020